Impacto das percepções de conflito no grupo e de bases de poder do médico sobre o estresse em profissionais de enfermagem - Costa, Daniele Tizo (2009)
Studies which come up to investigating the occupational stress generated by the relationship between the individual and the labor environment, where this stress is considered expensive to the worker s resources and a risk to his or her well-being, have been more and more often by the potential negative consequences to the worker, to the organization and even to the public health system. With the objective of contributing to the knowledge about occupational stress of nursery professionals, the current study aimed at identifying prediction relations between the perceptions which nursery professionals own about conflicts that happen in their groups of work and about the power used by doctors with whom they work, about their occupational stress. Furthermore, it was tried to deepen, through interviews, feelings about the job and the relationships with supervisor doctors and with workmates. The data was collected through valid and self- applicable scales. The ones who took part of the first phase were 124 voluntary nursery assistants and technicians, formally hired workers of a public university hospital, 77,4% were women and 22,6% were men, 57% had finished high-school. Considering all the participants, 58% presented with low levels of stress, whereas 14% noticed themselves as very or too stressed. The ones who took part of the second phase were four participants chosen at random among the ones who answered the first phase. The results of the first phase showed that the participants realized the existence of medium level of conflict inside the work teams. The legitimate power was base of power noticed to be the most used by doctors. The results of regression analysis showed that task conflict and coercion power were direct predictors of stress whereas age turned out to be the inverse predictor. The interviews were analyzed through the content analysis technique. Results indicated that the participants feel good in their jobs, like to work and don t feel stressed out. They consider as stress sources the overwork generated by their workmates lateness and lack of professionalism. The results corroborate other studies and the discussion compares these results with other studies. Appreciation to this study and future studies are suggested.